2018
DOI: 10.1111/cas.13479
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cells promote head and neck cancer progression through Periostin‐mediated phosphoinositide 3‐kinase/Akt/mammalian target of rapamycin

Abstract: Bone marrow mesenchymal stem cells (BMMSC) have been shown to be recruited to the tumor microenvironment and exert a tumor‐promoting effect in a variety of cancers. However, the molecular mechanisms related to the tumor‐promoting effect of BMMSC on head and neck cancer (HNC) are not clear. In this study, we investigated Periostin (POSTN) and its roles in the tumor‐promoting effect of BMMSC on HNC. In vitro analysis of HNC cells cultured in BMMSC‐conditioned media (MSC‐CM) showed that MSC‐CM significantly promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 36 publications
5
45
0
1
Order By: Relevance
“…Similar to our results, they did not observe signi cant effects of hDPSC-derived conditioned medium (CM) on in vitro HNSCC proliferation and therapeutic sensitivity, and in vivo tumour growth, despite the increase in tumour VEGF secretion(45). Con icting results on the impact of other MSC subtypes on in vitro and in vivo HNC cell proliferation, survival, migration, invasion and therapeutic sensitivity have previously been described(46)(47)(48)(49)(50)(51)(52)(53). These effects are mediated in a direct way via differentiation ofMSCs into malignant cells (54, 55), cancer-associated broblasts (CAFs) (56) and vascular-related cells (57, 58), or indirectly by (paracrine) interaction with immune cells (27, 59, 60), cancer stem cells (CSCs) (61-63), endothelial cells (24, 28, 64) and tumour cells (24, 30, 31, 65).…”
supporting
confidence: 89%
“…Similar to our results, they did not observe signi cant effects of hDPSC-derived conditioned medium (CM) on in vitro HNSCC proliferation and therapeutic sensitivity, and in vivo tumour growth, despite the increase in tumour VEGF secretion(45). Con icting results on the impact of other MSC subtypes on in vitro and in vivo HNC cell proliferation, survival, migration, invasion and therapeutic sensitivity have previously been described(46)(47)(48)(49)(50)(51)(52)(53). These effects are mediated in a direct way via differentiation ofMSCs into malignant cells (54, 55), cancer-associated broblasts (CAFs) (56) and vascular-related cells (57, 58), or indirectly by (paracrine) interaction with immune cells (27, 59, 60), cancer stem cells (CSCs) (61-63), endothelial cells (24, 28, 64) and tumour cells (24, 30, 31, 65).…”
supporting
confidence: 89%
“…Additionally, other ILs and cytokines secreted by MSCs promote tumor growth in different solid tumors and hematological malignancies (17,48). For example, in the conditioned medium of MSCs, periostin was found to promote the proliferation of head and neck cancer cells (49). On the other hand, IL-1β from the conditioned medium of FaDu cells mediates a proinflammatory and possibly protumorigenic response in MSCs (50).…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells and cancer cells have diverse interactions based on the histological origin of the latter. While the cancer-promoting effect of stem cells has been observed in malignancies such as breast cancer[ 69 ] as well as head and neck cancers,[ 70 ] the existing evidence has generally supported the use of transplanted NSCs and MSCs as safe therapeutic platforms to treat gliomas. Several recent studies have suggested their inhibitory effects against gliomas, such as the reported study of NSCs directly inhibiting the invasion and proliferation of gliomas[ 71 ] and their association with a survival benefit.…”
Section: B Asic R Ationale For mentioning
confidence: 99%